Theoretical Prediction of Thermoelectric Performance for Layered LaAgOX (X = S, Se) Materials in Consideration of the Four‐Phonon and Multiple Carrier Scattering Processes. Issue 3 (15th January 2023) - Bai, Shulin; Zhang, Jingyi; Wu, Mengxiu; Luo, Dongming; Wan, Da; Li, Xiaodong; Tang, Shuwei
Abstract: Inspired by the experimental achievement of layered LaCuOX (X = S, Se) with superior thermoelectric (TE) performance, the TE properties of Ag‐based isomorphic LaAgOX are systemically investigated by the first‐principles calculation. The LaAgOS and LaAgOSe are direct semiconductors with wide bandgaps of ≈2.50 and ≈2.35 eV. Essential four‐phonon and multiple carrier scattering mechanisms are considered in phonon and electronic transport calculations to improve the accuracy of the figure‐of‐merit ( ZT ). The p ‐type LaAgOX (X = S, Se) shows excellent TE performance on account of the large Seebeck coefficient originated from the band convergency and low thermal conductivity caused by the strong phonon–phonon scattering. Consequently, the optimal ZT s along the out‐of‐plane direction decrease in the order of n ‐type LaAgOSe (≈2.88) > p ‐type LaAgOSe (≈2.50) > p ‐type LaAgOS (≈2.42) > n ‐type LaAgOS (≈2.27) at 700 K, and the optimal ZT s of ≈1.16 and ≈1.29 are achieved for p ‐type LaAgOS and LaAgOSe at the same temperature. The present work would provide a deep insight into the phonon and electronic transport properties of LaAgOX (X = S, Se), but also could shed light on the way for the rational design of state‐of‐the‐art heteroanionic materials for TE application. Abstract : The crystal structure, electronic and phonon transport, and thermoelectric properties of layered LaAgOX (X = S, Se) are systematically analyzed using the first principles calculations. The optimal figure‐of‐merit ZT s of p ‐type LaAgOS and LaAgOSe are ≈1.16 and ≈1.29 at 700 K, which is comparable to most of the state‐of‐the‐art thermoelectric materials.